Evaluation of Si-Based Cells and the Importance of Scale-up. (29th August 2016) - Karulkar, Mohan; Wen, Hao; Kudla, Robert; Blaser, Rachel
Abstract : Automotive target metrics, which include specific and volumetric energy and power densities, are difficult to assess for many bench-scale materials. Thus, in order to identify the most promising technologies for future EV applications, it is crucial that researchers pursue scale-up to, in the least, a "pilot fab" scale that enables larger format cells and more relevant metric assessment. Several key processing differences have emerged during Ford's scale-up operations involving advanced lithium ion battery research, affecting every fabrication step, including mixing, coating, drying, calendaring, and cell assembly. Processing, in turn, affects key electrode characteristics like slurry formulation, active loading, density, adhesion, uniformity, and repeatability. In every case, scale-up improves processing and the associated electrode characteristics. Certain metrics are also very challenging to measure at small scales, including energy and power densities, effects of cell abuse, calendar life, electrolyte consumption, and volume expansion. This is detailed further with a silicon anode case study.